Effects of Chicory Fructans on Egg Cholesterol in Commercial Laying Hen - Chen, Y.C.; Nakthong, C.; Chen, T.C. (International Journal of Poultry Science, 2005)
Supplementing layer diets with oligofructose (1.0% (w/w) Raftifeed®OPS) and 1.0% (w/w) inulin (in the form of 1.3% (w/w) Raftifeed®IPE) reduced (P<0.05) yolk cholesterol concentrations on average by 18.64% and 16.44%, respectively, when compared to the control. However, greater reductions in yolk cholesterol content were calculated. They were 20.68% and 22.39%, on average, for oligofructose and inulin, respectively. These prebiotics reduced (P<0.05) laying hen`s blood serum cholesterol by 17.75% and 16.23%, respectively. At the same time, oligofructose and inulin increased (P<0.05) cholesterol concentrations of the small intestinal (jejunum) contents and total cholesterol excretion from the fecal material in layers compared with those of the controls. In studies of the linear relations of cholesterol concentrations in each pair of yolk, serum, jejunum contents, and fecal materials, the results indicated that lowered concentrations of yolk cholesterol might be attributed to lowered serum cholesterol that results from a greater content of unabsorbable cholesterol in jejunum contents and more cholesterol excretion. Hence, supplementation of a basal laying hen diet with either oligofructose or inulin reduced yolk cholesterol and may offer a way to produce eggs with lowered yolk cholesterol.